In vitro, in sacco and in vivo digestibility of ruminant feeds supplemented with herbs / Nik Fatihah Nik Abdullah - Nik Fatihah, Nik Abdullah (2016)
Animal feeds with added herb tested in in vitro, in sacco and in vivo techniques are the potential use combined with commercial pellets or PKE pellets to enhance the nutritive value of the feeds. Two types of herb mixture were tested. The mixture of local herbs (named as DD herbs): formulated in the Animal Biotechnology Laboratory University of Malaya (UM) and imported herb. The objective of the research was to compare DD herb potential in improving ruminant digestibility against imported herb. The experimental diets were formulated into 3 combination doses: 25 gm of herbs added to 975 gm of pallets (2.5% herbs added), 50 gm of herbs added to 950 gm of pallets (5.0% herbs added) and 75 gm of herbs added to 925 gm of pallets (7.5% herbs added). Each combination of mixed herb was tested separately but the same experimental procedures were employed. The highest digestibility of herbs in the in sacco and in vitro technique was tested using in vivo technique. In sacco experiments were conducted in the Institute Sciences of Biological Mini Farm (ISB), UM and the Animal Biotechnology Laboratory. Eleven replicates were tested in in sacco technique using six local goats with average age of 12 months fitted with rumen cannulae. The commercial pellet with DD herb animal feeds had the highest rate of digestion. The percentage of in sacco digestibility in 5.0% DD herb added commercial pellets and Napier grass (Pennisetum purpureum) was 67.47% at 24 hours, 69.61% at 48 hours, 69.83% at 72 hours and 74.63% at 96 hours. Same pellets and herb combination showed the highest rate of digestion results using in vitro digestibility technique. The 5.0% DD herb added commercial pellets and Napier grass in vitro digestibility was 68.39% at 24 hours, 73.50% at 48 hours, 78.29% at 72 hours and 80.22% at 96 hours. In the gas production experiments, the 5.0% DD herb gas production was higher than the other herb combination. The increase of DD herb produced a significant (p<0.5) increase in the digestibility percentage. However, increasing of the treatment to 7.5% DD herb had no significant effect on the percentage of digestibility. The laboratory findings of the in vitro and in sacco experiments were put to test in a field in vivo experiment using goats on a farm in Bidor, Perak to test digestibility of feeds and growth performance in goats. The experiment compared a group of kids fed diets containing DD herb versus fed control diets kids.